The Effect of Andalas (Morus macroura Miq.) Tree Bark Extract on Il-1β Gene Expression in the Pancreas of Hyperglycemic Rats - Hasnah, Widya Jummatul; Alioes, Yustini (Jurnal Kimia Riset, 2025)
Hyperglycemia is a medical condition characterized by elevated blood glucose levels above normal, which is a characteristic of several diseases, particularly diabetes mellitus (DM) and other conditions. In DM, hyperglycemia is associated with inflammation that increases TNF-α and IL-1β cytokines through NF-kB activation. DM treatment with antidiabetic drugs has side effects, such as diarrhea, vomiting, and peripheral edema, necessitating alternative therapies like andalas tree bark extract. This study aimed to determine the effect of andalas tree bark extract (Morus macroura Miq.) on IL-1β gene transcript expression in the pancreas of hyperglycemic rats. This experimental study utilized 24 rats divided into 6 groups: normal control (K-), hyperglycemic control (K+), metformin 500mg control (K), and three treatment groups(P1, P2, P3) with extract doses of 100, 200, and 300 mg/kgBW. Results showed that the mean IL-1β gene concentrations in K-, K+, K, P1, P2, and P3 were 0.09, 1.24, 0.38, 0.12, 1.12, and 1.76 respectively, with significant differences observed (p=0.032). The andalas tree bark extract (Morus macroura Miq.) was most effective at a dose of 100 mg/kg BW for reducing IL-1β expression, while a dose of 200 mg/kg BW was effective in reducing blood glucose levels and increasing body weight in hyperglycemic rats.